Survei Kelayakan Sarana dan Prasarana Olahraga Prestasi di Kabupaten Rembang pada Tahun 2021 - Ratna Tresnaning Ba'ib; Ricko Irawan (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the feasibility of achievement sports facilities and infrastructure in Rembang Regency in 2021. This study uses a qualitative approach. The object of this research is the facilities and infrastructure of badminton, volleyball, swimming, taekwondo, tennis, and football in Rembang Regency. Analysis of the data used is using data reduction, data display, and verifikasi. Based on the results of the study, it is known that badminton sports facilities and infrastructure are suitable for training and matches at the district level. Volleyball sports facilities and infrastructure are suitable for training and matches at the Residential level. Swimming sports facilities and infrastructure are suitable for training and selection at the Regency level. Taekwondo sports facilities and infrastructure are only suitable for practice. Tennis court sports facilities and infrastructure are only suitable for practice. Football sports facilities and infrastructure are not suitable for training or matches. The conclusion of this study is that in general the current sports facilities and infrastructure in Rembang Regency are suitable for use as training facilities and competitions at the regional level. For the national level competition, it is not feasible because the supporting facilities do not meet national standards and some of the infrastructure is in poor condition.